Polypropylene film for lithium battery current collector and preparation method thereof
By using the composite structure of modified polystyrene and isotactic polypropylene and cyclic olefin copolymer in the polypropylene film for lithium battery current collector, combined with the technical means of chemical bond grafting modified nano-silica, the polypropylene film has been solved. The problem of insufficient mechanical properties and high temperature resistance has been achieved, and higher mechanical properties and thermal stability have been achieved, making it suitable for lithium battery current collectors.
Patent Information
- Application Number
- CN202411180712.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The existing polypropylene films for current collectors of lithium batteries have shortcomings in terms of mechanical properties and high temperature resistance, which are difficult to meet the actual use needs.
Modified polystyrene and isotactic polypropylene are used as the upper and lower layers, and isotactic polypropylene and cyclic olefin copolymer are used as the middle layer. Nano-silica is modified through chemical bond grafting to improve the mechanical properties and thermal stability of the film.
The mechanical properties and dielectric properties of the polypropylene film are significantly improved, and the thermal stability is improved, making it more suitable for lithium battery current collectors.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer films, and in particular relates to a polypropylene film for lithium battery current collector and a preparation method thereof. Background Art
[0002] The current collector is an important component of lithium-ion batteries. It is not only a carrier for carrying battery active materials, but also a medium for transmitting current. It has a great impact on the performance of lithium batteries. An ideal current collector often needs to have comprehensive properties such as high conductivity, good stability, good mechanical strength, and low cost. Traditional current collectors composed of pure metal materials (aluminum foil, stainless steel, copper foil, nickel foil) have disadvantages such as heavy weight, high cost, and low safety. In order to improve the shortcomings of traditional current collectors, composite current collectors composed of organic polymers replacing part of metal materials have become a new development direction. Among them, polypropylene film is widely used in composite current collectors and other fields due to its advantages such as high breakdown field strength, low dielectric loss, excellent self-healing ability, ultra-thinness and low cost. However, polypropylene has poor compatibility with metals, and it itself has defects in mechanical properties and high temperature resistance, which makes it difficult to meet actual use needs.
[0003] A Chinese patent with application number 202210994379.7 discloses a high tensile strength polypropylene film for lithium battery current collector and a preparation method thereof. The polypropylene film is prepared by mixing polypropylene and modified polypyrrole. The polypropylene is modified by using modified polypyrrole. During the preparation of the polypropylene film, the carboxylate structure on the modified polypyrrole can induce polypropylene crystallization, thereby improving the mechanical properties of the polypropylene film to a certain extent. At the same time, the high-pressure air knife method is used to effectively control the roughness of the film surface, and the film is heat treated and relaxed after transverse and longitudinal stretching to ensure the thermal stability of the polypropylene film.
[0004] The Chinese patent application with application number 202310709758.1 discloses a modified polypropylene film and a preparation method thereof, a composite current collector and a preparation method thereof. The structure of the modified polypropylene film comprises a first surface layer, an intermediate layer and a second surface layer in sequence, wherein the components of the first surface layer and the second surface layer are composed of isotactic polypropylene, random polypropylene, polar additives, conductive particles, and a dispersant, and the components of the intermediate layer are composed of isotactic polypropylene, random polypropylene, polar additives, conductive particles, and a dispersant; by adjusting the appropriate ratio of isotactic polypropylene and random polypropylene, the two surface layers have better adhesion; the added conductive particles make the polypropylene film conductive, and a small amount of conductive particles can also serve as heterogeneous nucleation points to promote the crystallization of polypropylene, thereby improving the mechanical properties of the modified polypropylene film.
[0005] Although the above patents have improved the mechanical properties of polypropylene film through different methods, none of them involve the improvement of the heat resistance of polypropylene film. There is still room for improvement in its mechanical properties. Therefore, it is necessary to develop a polypropylene film with excellent comprehensive performance to meet market demand. Summary of the invention
[0006] The purpose of the present invention is to address the deficiencies in the prior art and provide a polypropylene film for lithium battery current collector and a preparation method thereof, wherein modified polystyrene and isotactic polypropylene are used as the upper and lower layers of the polypropylene film, and isotactic polypropylene and cycloolefin copolymer are used as the middle layer of the polypropylene film, so as to obtain a polypropylene film for lithium battery current collector with excellent mechanical properties and heat resistance.
[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0008] A polypropylene film for lithium battery current collector, the polypropylene film comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 70-80 parts of isotactic polypropylene and 20-25 parts of modified polystyrene; the components of the middle layer comprise 80-85 parts of isotactic polypropylene and 15-20 parts of cycloolefin copolymer;
[0009] Furthermore, the isotacticity of the isotactic polypropylene is greater than or equal to 95%, and the melt flow rate is 2.0-5.0 g / 10 min.
[0010] Furthermore, the mass fraction of norbornene in the cycloolefin copolymer is 50-66%, and the glass transition temperature of the cycloolefin copolymer is 125-145°C.
[0011] Furthermore, the thickness of the upper layer, the middle layer and the lower layer are all 3-4 μm.
[0012] Furthermore, the preparation method of the modified polystyrene is as follows: styrene, modified monomer, modified nano-silica and azobisisobutyronitrile are added into a polymerization tube, and after uniform mixing, nitrogen is replaced, the tube is sealed, the reaction temperature is maintained at 75-80°C, and the polymerization reaction is carried out for 20-24 hours to obtain modified polystyrene; the mass ratio of the styrene, modified monomer, modified nano-silica and azobisisobutyronitrile is 1:0.2-0.3:0.8-1:0.02-0.03. Furthermore, the preparation method of the modified monomer is as follows: add dichloromethane, sodium p-aminobenzenesulfonate and triethylamine to a reaction container, stir evenly, then slowly drop epichlorohydrin, after the dropwise addition, maintain the reaction temperature at 35-40° C., stir and react for 3-4 hours to obtain intermediate 1; further add toluene, intermediate 1, 5-hexenoic acid and p-toluenesulfonic acid to the reaction container, stir evenly, maintain the reaction temperature at 110° C., reflux and react for 4-5 hours to obtain the modified monomer.
[0013] The structural formula is: .
[0014] Furthermore, the preparation method of the modified nano-silicon dioxide is:
[0015] S1. Dispersing nano-silicon dioxide in a mixed solution of ethanol and water, adding 3-aminopropyltrimethoxysilane, adjusting the pH value of the mixed solution to about 6.5, maintaining the reaction temperature at 40-50° C., stirring the reaction for 5-6 hours, and after the reaction is completed, cooling and filtering, and repeatedly washing with ethanol, and drying to obtain amino nano-silicon dioxide; the mass ratio of the nano-silicon dioxide and 3-aminopropyltrimethoxysilane is 1:0.03-0.05; the volume ratio of ethanol and water in the mixed solution is 1-2:1;
[0016] S2. Disperse the amino-modified nano-silica in ethanol, add the modified monomer, stir evenly, adjust the pH value of the solution to about 8, maintain the reaction temperature at 50-60°C, react for 6-8 hours, and after the reaction is completed, cool and filter, and wash repeatedly with ethanol, and dry to obtain modified nano-silica; the mass ratio of the amino-modified nano-silica to the modified monomer is 1:0.2-0.3.
[0017] The present invention also provides a method for preparing a polypropylene film for a lithium battery current collector, comprising the following steps: mixing the components of an upper layer, a middle layer and a lower layer respectively according to a weight ratio, adding the components to a main machine and an auxiliary machine of a three-layer co-extrusion casting machine for melt extrusion to obtain a polypropylene film; and then biaxially stretching the polypropylene film to obtain a polypropylene film.
[0018] The present invention has the following beneficial effects:
[0019] The invention adopts styrene, modified nano silicon dioxide and modified monomer to prepare modified polystyrene. The modified nano silicon dioxide and the modified monomer both contain hexenyl ester groups and can participate in styrene polymerization. The modified monomer containing benzene sulfonic acid group and hexenyl ester group in the structure is grafted on the surface of the modified nano silicon dioxide. The benzene sulfonic acid group and the hexenyl ester group have good high temperature resistance and are helpful to improve the thermal stability of the film. Moreover, the modified monomer is a long-chain alkane sodium benzene sulfonate compound and has a certain dispersing effect, which is helpful to improve the uniform dispersion of the modified nano silicon dioxide in the modified polystyrene, thereby forming a modified polystyrene with uniform and stable structure.
[0020] The present invention grafts the modified nano silicon dioxide to the modified polystyrene molecules through chemical bonds, and has better interface compatibility with isotactic polypropylene, so that the nano silicon dioxide can be evenly dispersed in the film. Since the modified monomer containing benzenesulfonic acid groups is grafted on the surface of the modified nano silicon dioxide, the nano silicon dioxide can work together with other benzene ring structures in the modified polystyrene, and promote the arrangement of isotactic polypropylene chain segments through CH-π interaction, thereby effectively promoting the nucleation crystallization of isotactic polypropylene, and greatly improving the mechanical properties and dielectric properties of the film; at the same time, the high temperature resistant benzenesulfonic acid groups and hexenyl ester groups in the modified polystyrene can also improve the thermal stability of the film.
[0021] The present invention uses modified polystyrene and isotactic polypropylene as the upper and lower layers of the polypropylene film, and isotactic polypropylene and cycloolefin copolymer as the middle layer of the polypropylene film. The prepared composite polypropylene film has good mechanical properties and dielectric properties, high thermal stability, and is more suitable for lithium battery current collectors. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In the technical scheme of the present invention, the chemical reagents used are all commonly available on the market, wherein the isotacticity of isotactic polypropylene is greater than or equal to 95%, and the melt flow rate is 2.0-5.0 g / 10 min, and the isotacticity of isotactic polypropylene is 97%, and the melt flow rate is 3.5 g / 10 min; the mass fraction of norbornene in the cycloolefin copolymer is 50-66%, the glass transition temperature of the cycloolefin copolymer is 125-145°C, and the cycloolefin copolymer is Mitsui Chemicals APL5014; styrene CAS No. 100-42-5; azobisisobutyronitrile CAS No. 78-67-1; 3-aminopropyltrimethoxysilane CAS No. 13822-56-5; epichlorohydrin CAS No. 106-89-8; sodium p-aminobenzenesulfonate CAS No. 515-74-2; 5-hexenoic acid CAS No. 1577-22-6; p-toluenesulfonic acid CAS No. 104-15-4.
[0024] In the technical solution of the present invention, the synthetic route of the modified monomer is as follows:
[0025]
[0026] 500 mL of dichloromethane, 20.0 g of sodium p-aminobenzenesulfonate and 15.4 g of triethylamine were added to the reaction container, stirred evenly, and then 10.3 g of epichlorohydrin was slowly added dropwise. After the dropwise addition, the reaction temperature was maintained at 35-40° C., and the reaction was stirred for 3-4 hours. After the reaction was completed, it was filtered, and the solid was dried to obtain 30.0 g of intermediate 1; 500 mL of toluene, 30.0 g of intermediate 1, 11.6 g of 5-hexenoic acid and 0.87 g of p-toluenesulfonic acid were added to the reaction container, stirred evenly, and the reaction temperature was maintained at 110° C. The reaction was refluxed for 4-5 hours. After the reaction was completed, toluene was removed, and water and dichloromethane were used for extraction. The aqueous phase was collected and concentrated under reduced pressure to obtain 31.6 g of modified monomer, wherein the molar ratio of sodium p-aminobenzenesulfonate, epichlorohydrin, triethylamine, 5-hexenoic acid and p-toluenesulfonic acid was 1:1.1:1.5:1:0.05.
[0027] Modified monomer: ESI (m / z): 384.8 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 9.53 (s, 1H), 7.34 (d, J=8.6Hz, 2H), 7.22 (d, J=8.6Hz, 2H), 5.56-5.60 (m, 2H), 4. 88-4.93 (m, 2H), 3.73-3.76 (m, 1H), 3.43-3.47 (m, 2H), 3.15-3.17 (m, 1H), 2.25-2.30 (m, 4H), 1.76-1.79 (m, 2H).
[0028] Example 1
[0029] A polypropylene film for lithium battery current collector, comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 80 parts of isotactic polypropylene and 23 parts of modified polystyrene; the components of the middle layer comprise 85 parts of isotactic polypropylene and 20 parts of cycloolefin copolymer; the thickness of the upper layer, the middle layer and the lower layer are all 4 μm.
[0030] A method for preparing a polypropylene film for a lithium battery current collector comprises the following steps: respectively mixing components of an upper layer, a middle layer and a lower layer evenly according to a weight ratio, adding the components to a main machine and an auxiliary machine of a three-layer co-extrusion casting machine for melt extrusion to obtain a polypropylene film; then biaxially stretching the polypropylene film to obtain a polypropylene film; wherein the melt extrusion temperature is 240°C; during biaxial stretching, the longitudinal stretching temperature is 150°C and the stretching ratio is 5 times; the transverse stretching temperature is 160°C and the stretching ratio is 6 times.
[0031] The preparation method of modified polystyrene is as follows: styrene, modified monomer, modified nano-silica and azobisisobutyronitrile are added into a polymerization tube, and after being evenly mixed, nitrogen is replaced, the tube is sealed, and the reaction temperature is maintained at 80° C., and the polymerization reaction is carried out for 20 hours to obtain modified polystyrene; the mass ratio of styrene, modified monomer, modified nano-silica and azobisisobutyronitrile is 1:0.3:1:0.03.
[0032] The preparation method of modified nano silicon dioxide is:
[0033] S1. Dispersing nano-silica in a mixed solution of ethanol and water, adding 3-aminopropyltrimethoxysilane, adjusting the pH value of the mixed solution to about 6.5, maintaining the reaction temperature at 50°C, stirring the reaction for 5 hours, and after the reaction is completed, cooling and filtering, and repeatedly washing with ethanol, and drying to obtain amino nano-silica; the mass ratio of nano-silica to 3-aminopropyltrimethoxysilane is 1:0.04; the volume ratio of ethanol to water in the mixed solution is 2:1; the mass ratio of nano-silica to the mixed solution is 1:50;
[0034] S2. Disperse the amino-modified nano-silica in ethanol, add the modified monomer, stir evenly, adjust the pH value of the solution to about 8, maintain the reaction temperature at 50°C, react for 8 hours, and after the reaction is completed, cool and filter, and wash repeatedly with ethanol, and obtain modified nano-silica after drying; the mass ratio of amino-modified nano-silica to modified monomer is 1:0.3; the amount of ethanol used is 25 times the mass of amino-modified nano-silica.
[0035] Example 2
[0036] A polypropylene film for lithium battery current collector, comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 75 parts of isotactic polypropylene and 25 parts of modified polystyrene; the components of the middle layer comprise 80 parts of isotactic polypropylene and 18 parts of cycloolefin copolymer; the thickness of the upper layer, the middle layer and the lower layer are all 3.5 μm.
[0037] The preparation method of a polypropylene film for lithium battery current collector is the same as that in Example 1.
[0038] The preparation method of modified polystyrene is as follows: styrene, modified monomer, modified nano-silica and azobisisobutyronitrile are added into a polymerization tube, and after being evenly mixed, nitrogen is replaced, the tube is sealed, and the reaction temperature is maintained at 75° C., and the polymerization reaction is carried out for 24 hours to obtain modified polystyrene; the mass ratio of styrene, modified monomer, modified nano-silica and azobisisobutyronitrile is 1:0.25:0.8:0.02.
[0039] The preparation method of modified nano silicon dioxide is:
[0040] S1. Dispersing nano-silica in a mixed solution of ethanol and water, adding 3-aminopropyltrimethoxysilane, adjusting the pH value of the mixed solution to about 6.5, maintaining the reaction temperature at 40°C, stirring the reaction for 6 hours, and after the reaction is completed, cooling and filtering, and repeatedly washing with ethanol, and drying to obtain amino nano-silica; the mass ratio of nano-silica to 3-aminopropyltrimethoxysilane is 1:0.05; the volume ratio of ethanol and water in the mixed solution is 1:1; the mass ratio of nano-silica to the mixed solution is 1:50;
[0041] S2. Disperse the amino-modified nano-silica in ethanol, add the modified monomer, stir evenly, adjust the pH value of the solution to about 8, maintain the reaction temperature at 60°C, react for 6 hours, and after the reaction is completed, cool and filter, and wash repeatedly with ethanol, and obtain modified nano-silica after drying; the mass ratio of amino-modified nano-silica to modified monomer is 1:0.25; the amount of ethanol used is 25 times the mass of amino-modified nano-silica.
[0042] Example 3
[0043] A polypropylene film for lithium battery current collector, comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 70 parts of isotactic polypropylene and 20 parts of modified polystyrene; the components of the middle layer comprise 83 parts of isotactic polypropylene and 15 parts of cycloolefin copolymer; the thickness of the upper layer, the middle layer and the lower layer are all 3 μm.
[0044] The preparation method of a polypropylene film for lithium battery current collector is the same as that in Example 1.
[0045] The preparation method of modified polystyrene is as follows: styrene, modified monomer, modified nano-silica and azobisisobutyronitrile are added into a polymerization tube, and after being evenly mixed, nitrogen is replaced, the tube is sealed, and the reaction temperature is maintained at 80° C., and the polymerization reaction is carried out for 24 hours to obtain modified polystyrene; the mass ratio of styrene, modified monomer, modified nano-silica and azobisisobutyronitrile is 1:0.2:0.9:0.03.
[0046] The preparation method of modified nano silicon dioxide is:
[0047] S1. Disperse nano-silica in a mixed solution of ethanol and water, add 3-aminopropyltrimethoxysilane, adjust the pH value of the mixed solution to about 6.5, maintain the reaction temperature at 45°C, stir the reaction for 5.5 hours, and after the reaction is completed, cool and filter, wash repeatedly with ethanol, and dry to obtain amino nano-silica; the mass ratio of nano-silica to 3-aminopropyltrimethoxysilane is 1:0.03; the volume ratio of ethanol to water in the mixed solution is 1.5:1; the mass ratio of nano-silica to the mixed solution is 1:50;
[0048] S2. Disperse the amino-modified nano-silica in ethanol, add the modified monomer, stir evenly, adjust the pH value of the solution to about 8, maintain the reaction temperature at 55°C, react for 7 hours, and after the reaction is completed, cool and filter, and wash repeatedly with ethanol, and obtain modified nano-silica after drying; the mass ratio of amino-modified nano-silica to modified monomer is 1:0.2; the amount of ethanol used is 25 times the mass of amino-modified nano-silica.
[0049] Example 4
[0050] A polypropylene film for lithium battery current collector, comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer include 80 parts of isotactic polypropylene and 23 parts of modified polystyrene; the components of the lower layer include 75 parts of isotactic polypropylene and 25 parts of modified polystyrene; the components of the middle layer include 83 parts of isotactic polypropylene and 15 parts of cycloolefin copolymer; the thickness of the upper layer and the lower layer is 4 μm; the thickness of the middle layer is 3 μm.
[0051] The preparation method of a polypropylene film for lithium battery current collector is the same as that in Example 1.
[0052] The preparation method of modified polystyrene is the same as that in Example 1.
[0053] The preparation method of modified nano silicon dioxide is:
[0054] S1, the same as step S1 in Example 2;
[0055] S2. Same as step S2 in Example 3.
[0056] Comparative Example 1
[0057] Compared with Example 1, this comparative example uses nano-silicon dioxide in the preparation method of modified polystyrene.
[0058] A polypropylene film for lithium battery current collector, comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 80 parts of isotactic polypropylene and 23 parts of modified polystyrene; the components of the middle layer comprise 85 parts of isotactic polypropylene and 20 parts of cycloolefin copolymer; the thickness of the upper layer, the middle layer and the lower layer are all 4 μm.
[0059] The preparation method of a polypropylene film for lithium battery current collector is the same as that in Example 1.
[0060] The preparation method of modified polystyrene is as follows: styrene, modified monomer, nano-silica and azobisisobutyronitrile are added into a polymerization tube, and after uniform mixing, nitrogen is replaced, the tube is sealed, and the reaction temperature is maintained at 80° C., and the polymerization reaction is carried out for 20 hours to obtain modified polystyrene; the mass ratio of styrene, modified monomer, nano-silica and azobisisobutyronitrile is 1:0.3:1:0.03.
[0061] Comparative Example 2
[0062] Compared with Example 1, this comparative example does not use a modified monomer in the preparation method of the modified polystyrene.
[0063] A polypropylene film for lithium battery current collector, comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 80 parts of isotactic polypropylene and 23 parts of modified polystyrene; the components of the middle layer comprise 85 parts of isotactic polypropylene and 20 parts of cycloolefin copolymer; the thickness of the upper layer, the middle layer and the lower layer are all 4 μm.
[0064] The preparation method of a polypropylene film for lithium battery current collector is the same as that in Example 1.
[0065] The preparation method of modified polystyrene is as follows: styrene, modified nano-silica and azobisisobutyronitrile are added into a polymerization tube, mixed evenly, replaced with nitrogen, sealed, maintained at a reaction temperature of 80°C, and polymerized for 20 hours to obtain modified polystyrene; the mass ratio of styrene, modified nano-silica and azobisisobutyronitrile is 1:1:0.03.
[0066] The preparation method of modified nano-silicon dioxide is the same as that in Example 1.
[0067] Comparative Example 3
[0068] Compared with Example 1, polystyrene is used in the components of both the upper layer and the lower layer in this comparative example.
[0069] A polypropylene film for lithium battery current collector, comprising an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 80 parts of isotactic polypropylene and 23 parts of polystyrene; the components of the middle layer comprise 85 parts of isotactic polypropylene and 20 parts of cycloolefin copolymer; the thickness of the upper layer, the middle layer and the lower layer are all 4 μm.
[0070] The preparation method of a polypropylene film for lithium battery current collector is the same as that in Example 1.
[0071] The preparation method of polystyrene is as follows: add styrene and azobisisobutyronitrile into a polymerization tube, mix them evenly, replace nitrogen, seal the tube, maintain the reaction temperature at 80°C, perform polymerization reaction for 20 hours, and obtain polystyrene; the mass ratio of styrene to azobisisobutyronitrile is 1:0.03.
[0072] The polypropylene films prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests, wherein the tensile strength and elongation at break were measured in accordance with GB / T 13542.2; the thermal shrinkage was measured in accordance with GB / T 13542.2, and the test conditions were 15 min in an oven at 120°C; the dielectric properties were measured in accordance with GB / T 1409; the test results are shown in Table 1.
[0073] Table 1 Performance test results of polypropylene film
[0074]
[0075] From the results in Table 1, it can be seen that the polypropylene films prepared in Examples 1-4 of the present invention have higher tensile strength, elongation at break, dielectric loss factor and breakdown strength, and lower thermal shrinkage, indicating that they have good mechanical properties, dielectric properties and high thermal stability.
[0076] Compared with comparative examples 1-3, in Example 1 of the present invention, styrene, modified nano-silica and modified monomers are used in the preparation method of modified polystyrene. The modified nano-silica and the modified monomers both contain hexenyl ester groups and can participate in styrene polymerization, wherein the modified monomer containing benzene sulfonic acid groups and hexenyl ester groups in the structure is grafted on the surface of the modified nano-silica. The benzene sulfonic acid groups and the hexenyl ester groups have good high temperature resistance and help to improve the thermal stability of the film. Moreover, the modified monomer is a long-chain alkane sodium benzene sulfonate compound, which has a certain dispersing effect and helps to improve the uniform dispersion of the modified nano-silica in the modified polystyrene, thereby forming a modified polystyrene with uniform and stable structure. In the present invention, the modified polystyrene is composited with isotactic polypropylene as the upper and lower layers of the polypropylene film, and the modified nano-silica is grafted into the modified polystyrene molecules through chemical bonds, and has better interface compatibility with the isotactic polypropylene, so that it can be evenly dispersed in the film, which helps to effectively promote the nucleation and crystallization of the isotactic polypropylene, thereby greatly improving the mechanical properties and dielectric properties of the film.
[0077] It should be noted that, in this document, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Although the embodiments of the present application have been shown and described, it is understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A polypropylene film for lithium battery current collector, characterized in that: The polypropylene film comprises an upper layer, a middle layer and a lower layer; in parts by weight, the components of the upper layer and the lower layer each comprise 70-80 parts of isotactic polypropylene and 20-25 parts of modified polystyrene; the components of the middle layer comprise 80-85 parts of isotactic polypropylene and 15-20 parts of cycloolefin copolymer; The preparation method of the modified polystyrene is as follows: styrene, modified monomer, modified nano-silica and azobisisobutyronitrile are added into a polymerization tube, and after being uniformly mixed, nitrogen is replaced, the tube is sealed, and the reaction temperature is maintained at 75-80° C., and the polymerization reaction is carried out for 20-24 hours to obtain the modified polystyrene; the structural formula of the modified monomer is: ; The preparation method of the modified nano silicon dioxide is: S1. Disperse nano-silica in a mixed solution of ethanol and water, add 3-aminopropyltrimethoxysilane, adjust the pH value of the mixed solution to 6.5, maintain the reaction temperature at 40-50° C., stir the reaction for 5-6 hours, and after the reaction is completed, cool and filter, wash repeatedly with ethanol, and dry to obtain amino-modified nano-silica; S2. Disperse the amino-modified nano-silica in ethanol, add the modified monomer, stir evenly, adjust the pH value of the solution to 8, maintain the reaction temperature at 50-60°C, react for 6-8 hours, and after the reaction is completed, cool and filter, and wash repeatedly with ethanol, and dry to obtain modified nano-silica.
2. The polypropylene film for lithium battery current collector according to claim 1, characterized in that: The mass ratio of the nano-silicon dioxide and 3-aminopropyltrimethoxysilane in step S1 is 1:0.03-0.05; the volume ratio of ethanol and water in the mixed solution is 1-2:
1.
3. The polypropylene film for lithium battery current collector according to claim 1, characterized in that: The mass ratio of the amino-modified nano-silica to the modified monomer in step S2 is 1:0.2-0.
3.
4. The polypropylene film for lithium battery current collector according to claim 1, characterized in that: In the preparation method of modified polystyrene, the mass ratio of styrene, modified monomer, modified nano-silicon dioxide and azobisisobutyronitrile is 1:0.2-0.3:0.8-1:0.02-0.
03.
5. The polypropylene film for lithium battery current collector according to claim 1, characterized in that: The isotacticity of the isotactic polypropylene is greater than or equal to 95%, and the melt flow rate is 2.0-5.0 g / 10 min.
6. The polypropylene film for lithium battery current collector according to claim 1, characterized in that: The mass fraction of norbornene in the cycloolefin copolymer is 50-66%, and the glass transition temperature of the cycloolefin copolymer is 125-145°C.
7. The polypropylene film for lithium battery current collector according to claim 1, characterized in that: The thickness of the upper layer, the middle layer and the lower layer are all 3-4 μm.
8. A method for preparing a polypropylene film for lithium battery current collector according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the components of the upper layer, the middle layer and the lower layer respectively according to the weight ratio, adding the components to the main machine and the auxiliary machine of the three-layer co-extrusion casting machine for melt extrusion to obtain a polypropylene membrane; and then biaxially stretching the polypropylene membrane to obtain a polypropylene film.
Citation Information
Patent Citations
Smelting process
CA100425A
Toilet article
CA125145A
High-tensile-strength polypropylene film for lithium battery current collector and preparation method of high-tensile-strength polypropylene film
CN115340725A
Modified polypropylene film and preparation method thereof, and composite current collector and preparation method thereof
CN116922907A
Anionic-nonionic surfactant and preparation method thereof
CN108479631A
Cited By
Preparation method of multi-layer co-extrusion composite insulating material
CN120228981A
A method for preparing multi-layer co-extruded composite insulation material
CN120228981B
Biaxially oriented polypropylene film for composite copper foil and manufacturing method of biaxially oriented polypropylene film
CN122255531A